The Challenges of Controlling and IT Support in Non-financial Reporting - Osmanagić Bedenik, Nidžara; Prebežac, Darko; Strugar, Ivan; Barišić, Petra (International Journal of Industrial Engineering and Management, 2019)
It is nowadays becoming increasingly clear that financial reporting can no longer be sufficient when it comes to business reporting. In that sense, the non-financial reporting is a ‘must’ in the modern economy for different groups of the general public as it reflects the responsibility of a company to conduct business activities in a sustainable way. The non-financial reporting represents relatively new area of research, and very little research has investigated the role of controlling and IT support in nonfinancial reporting. Therefore, the aim of this study was to find the best business practices and reveale the role of controlling and IT support in the process of preparing and publishing nonfinancial reports in hotel companies in Croatia. We applied the case study approach on the hotel company Ilirija d.d. The results show that the role of controlling in Ilirija d.d. is most significant in the economic field, and it is of great importance both in the ecological and social spheres; while the IT has a significant role in preparing and tracking data for non-financial reporting. Article history: Received (03.12.2018); Revised (08.01.2019); Accepted (13.02.2019)